Arthroscopic Lavage and Implantation of Gentamicin-impregnated Collagen Sponges for Treatment of Chronic Septic Arthritis in Cattle - Steiner, A.; Hirsbrunner, G.; Miserez, R.; Tschudi, P. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The object of this retrospective clinical study was to evaluate the efficacy of arthroscopic lavage and debridement, followed by intra-articular implantation of resorbable gentamicin-impregnated collagen sponges (GICS) for treatment of chronic (≥ seven days) septic arthritis in cattle. Fourteen cattle suffering from chronic septic monarthritis refractory to previous treatment were included in this study. Age ranged from one month to 7 years (mean = 34 months) and bodyweight from 58 to 640 kg (mean = 422 kg). The degree of lameness and characteristics of synovial fluid were evaluated before and at days #10 and 20 after the initial operation. The standard surgical procedure consisted of arthroscopic “through-and-through” lavage of the affected joint with a physiological Ringer’s solution, partial synovectomy, and curettage of the articular cartilage when considered necessary, followed by the intra-articular administration of GICS. The aftercare included administration of procaine penicillin, phenylbutazone, and stall confinement. The progress of the cases was monitored at three to 24 months after the initial operation.The tarsocrural joint was affected in six cases, the antebrachiocarpal joint in five and the metacarpophalangeal joint in three cases. The degree of lameness, total nucleated cell count and total protein of synovial fluid significantly (P <.05) decreased within 10 days after the operation. Treatment was successful in 12 of 14 animals (86%). It was therefore concluded that the implantation of GICS after routine “throughand- through” lavage is a valuable alternative technique for the treatment of chronic septic arthritis in cattle. A subsequent second operation for implant removal was not necessary, as GICS are fully absorbable. The tarsocrural joint is associated with the least favourable prognosis of the joints treated in this study.The efficacy of arthroscopic “through-and-through” lavage and debridement, followed by intra-articular implantation of absorbable gentamicin-impreg-nated collagen sponges (GICS) for treatment of chronic (≥ seven days) septic arthritis in cattle was evaluated. Treatment was successful in 12 of 14 cattle (86%). This suggests that the described technique is a valuable alternative to established treatment regimens for prolonged intra-articular administration of gentamicin. When compared to gentamicin-impregnated polymethylmethacrylate beads, GICS have the advantage that a second operation for implant removal is not necessary.
Keywords: Cattle; septic arthritis; gentamicin-impregnated collagen sponges; arthroscopy